Synthesis and structural analysis of a new polymorph of [CuII(PMDETA)Br2]. Issue 5 (4th May 2017) - Fakharzadeh Kermani, Samira; Afshar Taromi, Faramarz; Eslami, Hormoz; Notash, Behrouz
ABSTRACT: A new polymorph of [Cu II (PMDETA)Br2 ] has been recognized and characterized by X-ray structural studies at two different temperatures (120 and 298°K). The results indicated the existence of a monoclinic crystalline system for [Cu II (PMDETA)Br2 ] grown in CH3 OH or CH3 CN with a distorted square pyramid geometry. The supramolecular structure of this complex has been studied using geometrical and Hirshfeld surface analysis. From lattice energy calculation, it has been shown that the newly found polymorph is thermodynamically more stable than the previously recognized one. UV-vis spectroscopy confirmed complex formation between Cu II Br2 and PMDETA in CH3 OH and CH3 CN, which was accompanied by peak displacement. FTIR spectroscopy, differential scanning calorimetry, and scanning electron microscopy were also used to get insights about the formation of this new polymorph of [Cu II (PMDETA)Br2 ].